An in situ reactivation study reveals the supreme stability of γ-alumina for the oxidative dehydrogenation of ethylbenzene to styrene. Issue 15 (6th July 2018) - Melián-Cabrera, Ignacio; Zarubina, Valeriya; Nederlof, Christiaan; Kapteijn, Freek; Makkee, Michiel
Abstract : Ethylbenzene oxidative dehydrogenation over γ-alumina under in situ conditions has revealed that the catalyst recovers fully the original conversion and selectivity under steady state conditions. Abstract : Ethylbenzene oxidative dehydrogenation over γ-alumina under in situ conditions has revealed that the catalyst recovers fully the original conversion and selectivity under steady state conditions. In the transition state, the reactivated catalyst achieved the steady state conditions faster. This was supported by the physico-chemical characterisation that revealed pore widening due to crystallite sintering during the reactivation, which has a beneficial effect. The excellent stability after the reactivation recycle, as well as along the run, shows the great promise of this catalyst.